Rapid evaluation method for turbidity of nitric oxide reducing agent urea aqueous solution

By using anion dispersant and cationic adsorbent to disperse and adsorb the insoluble objects in the urea the aquatic solution of nitrogen oxides, solve the problems of complex detection, long time, and inaccurate results in existing technologies, realize fast and accurate accuracy Turbidity detection.

CN119334822AActive Publication Date: 2025-01-21SHANDONG NEW BLUE ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411864003.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

In the prior art, the quality detection method of the nitrogen oxide reducing agent urea aqueous solution is complicated, and it takes a long time and has the problem of low or high detection results, especially the accuracy and speed of detection of insoluble substance content.

Method used

Under anion dispersant and cationic adsorbent, disperse and adsorb the insoluble objects in the urea water solution of nitrogen oxide reducing agent. And to calculate the turbidity through a linear fit formula.

Benefits of technology

It can quickly and accurately detect the turbidity of the urea aquatic solution of nitrogen oxide reducing agent without dependence on turbidity. The detection result is smallly affected by the temperature. The error rate is between 0.63-2.00%, which significantly shortens the detection time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for rapidly evaluating the turbidity of a nitrogen oxide reducing agent urea aqueous solution, and belongs to the technical field of urea aqueous solution detection.The method comprises the steps that 1000 g of a sample is taken from the nitrogen oxide reducing agent urea aqueous solution to be detected, 100 mg of an anionic dispersant is added, stirring is conducted for 5 min at the room temperature, then 2000 mg of a cationic adsorbent is added, stirring is conducted for 5 min at the room temperature, and finally the turbidity of the nitrogen oxide reducing agent urea aqueous solution to be detected is obtained. The method comprises the following steps: weighing a dried mixed cellulose ester film with the filtering precision of 5 microns, filtering, drying the filtered mixed cellulose ester film, weighing, calculating the weight change which is the content of insoluble substances in every 1000g of a to-be-measured nitrogen oxide reducing agent urea water solution, and calculating the turbidity according to the content of the insoluble substances and a linear fitting formula, according to the method, the turbidity of the nitric oxide reducing agent urea aqueous solution can be rapidly detected without depending on a turbidimeter, the detection result is accurate, and the method is slightly influenced by temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of urea aqueous solution detection, and in particular to a method for quickly evaluating the turbidity of a urea aqueous solution containing a nitrogen oxide reducing agent. Background Art

[0002] Nitrogen oxide reducing agent urea aqueous solution refers to an aqueous solution prepared from AUS 32 special urea and pure water without any other additives, in which the mass concentration of urea is 32.5%. Nitrogen oxide reducing agent urea aqueous solution is also called automotive urea aqueous solution. For diesel vehicles such as heavy trucks and buses to meet the National VI emission standards, a suitable SCR system (selective catalytic reduction system) is required for exhaust gas treatment. Nitrogen oxide reducing agent urea aqueous solution can treat exhaust gas through the SCR system. The working principle is that the nitrogen oxide reducing agent urea aqueous solution undergoes pyrolysis and hydrolysis at high temperature to produce ammonia, and ammonia reduces nitrogen oxides in the exhaust gas to pollution-free nitrogen and water. Nitrogen oxide reducing agent urea aqueous solution can not only effectively reduce exhaust emissions and avoid environmental pollution, but also significantly reduce diesel consumption and save costs.

[0003] There are two main methods for preparing the urea aqueous solution of nitrogen oxide reducing agent. Among them, the first preparation method is to purify industrial-grade urea, and utilize that the urea in the urea aqueous solution will hydrolyze at 70-75°C and crystallize at below 30°C. Through multiple hydrolysis and crystallization, the purity of urea is improved to obtain AUS 32 special urea, and then mix it with pure water to prepare the urea aqueous solution of nitrogen oxide reducing agent. The second preparation method is to directly prepare the urea aqueous solution of nitrogen oxide reducing agent through urea molten liquid.

[0004] However, the NOx reducing agent urea aqueous solution on the market currently has the problem of uneven quality. Specifically, some NOx reducing agent urea aqueous solution manufacturers use inferior urea raw materials or substandard pure water, resulting in impurities in the prepared NOx reducing agent urea aqueous solution, which further leads to unstable quality of the prepared NOx reducing agent urea aqueous solution. In severe cases, it may also cause damage to components in the vehicle's SCR system.

[0005] In order to ensure the quality of urea aqueous solution as nitrogen oxide reducing agent, my country implemented the national standard GB 29518-2013 "Urea aqueous solution as nitrogen oxide reducing agent for diesel engines (AUS 32)" on July 1, 2013. This standard stipulates the urea content, density, refractive index, impurity content and determination method in urea aqueous solution as nitrogen oxide reducing agent. Among them, the impurity content includes alkalinity, biuret content, formaldehyde content, insoluble matter content, phosphate content, calcium content, iron content, copper content, zinc content, chromium content, nickel content, aluminum content, magnesium content, sodium content and potassium content.

[0006] For the insoluble content, according to the determination method specified in the national standard GB 29518-2013 "Urea Aqueous Solution for Nitrogen Oxide Reductant in Diesel Engines (AUS 32)", it is necessary to take a sample of the urea aqueous solution of nitrogen oxide reductant to be tested and weigh it, shake the sample thoroughly to keep it uniform, then add it to a glass and mix it with water, select a filter membrane, weigh the filter membrane and filter it with the filter membrane, then wash the glass several times, filter the washing liquid with the filter membrane, dry and weigh the filtered filter membrane, calculate the mass of insoluble matter according to the weight change of the filter membrane, and further calculate the insoluble content. However, the above determination method is too complicated, and the glass needs to be washed and filtered several times. In addition, a filter membrane with high filtration accuracy is used for filtration, and the filtration speed is slow, resulting in a long detection time. In addition, there is a situation where the cleaning is not thorough during the detection, resulting in a low test result, and multiple tests are required.

[0007] Turbidity refers to the degree of obstruction of a solution to the passage of light, which includes the scattering of light by insoluble matter and the absorption of light by solute molecules. Turbidity is usually used to determine the quality of natural water, drinking water and some industrial water. As for the turbidity of the urea aqueous solution of nitrogen oxide reducing agent, since urea is colorless after being dissolved in water, the influencing factor of the turbidity of the urea aqueous solution of nitrogen oxide reducing agent is mainly the insoluble content in the urea aqueous solution of nitrogen oxide reducing agent. After further testing, it was found that the turbidity range of the urea aqueous solution of nitrogen oxide reducing agent that meets the requirements of the insoluble content in the national standard GB 29518-2013 "Urea aqueous solution of nitrogen oxide reducing agent for diesel engine (AUS32)" is 0.2-24NTU. When the turbidity of the urea aqueous solution of nitrogen oxide reducing agent exceeds 24NTU, it means that the insoluble content in the urea aqueous solution of nitrogen oxide reducing agent does not meet the requirements of the insoluble content in the national standard GB 29518-2013 "Urea aqueous solution of nitrogen oxide reducing agent for diesel engine (AUS32)". Therefore, whether the insoluble matter content in the nitrogen oxide reducing agent urea aqueous solution meets the standard requirements can be determined by measuring the turbidity of the nitrogen oxide reducing agent urea aqueous solution.

[0008] The following problems exist in the detection of the turbidity of the aqueous solution of urea, a nitrogen oxide reducing agent: first, before using the turbidity meter, it is necessary to calibrate, preheat, prepare samples, perform zero-point calibration on the samples, and calibrate the standard solution, resulting in a long detection time; second, it is necessary to rely on a turbidity meter for detection, and the accuracy of the turbidity meter has a great influence on the detection results; third, the detection results of the turbidity meter are greatly affected by temperature.

[0009] In response to the above problems, the inventors have tried a method in which an adsorbent is used to adsorb the insoluble matter in the nitrogen oxide reducing agent urea aqueous solution, the adsorbent is weighed after adsorption, and then the insoluble matter content in the nitrogen oxide reducing agent urea aqueous solution is calculated. However, during the adsorption, the selective adsorption capacity of the adsorbent used is poor, and the urea in the nitrogen oxide reducing agent urea aqueous solution is adsorbed, resulting in a high detection result of the insoluble matter content. Furthermore, the inventors have tried a method in which an anionic surfactant is first added to the nitrogen oxide reducing agent urea aqueous solution, the insoluble matter in the nitrogen oxide reducing agent urea aqueous solution is coated with the anionic surfactant, and then an adsorbent with a cationic charge is used for adsorption. However, due to the high solubility of the anionic surfactant in water, when the adsorbent with a cationic charge is used for adsorption, part of the anionic surfactant that has not coated the insoluble matter cannot be adsorbed, resulting in a low detection result of the insoluble matter content. Summary of the invention

[0010] In view of the deficiencies in the prior art, the present invention provides a method for quickly evaluating the turbidity of a nitrogen oxide reducing agent urea aqueous solution, which can quickly detect the turbidity of a nitrogen oxide reducing agent urea aqueous solution without relying on a turbidimeter, and the detection result is accurate and is less affected by temperature.

[0011] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for rapidly evaluating the turbidity of a nitrogen oxide reducing agent urea aqueous solution comprises taking 1000 g of a sample from the nitrogen oxide reducing agent urea aqueous solution to be tested, adding 100 mg of an anionic dispersant, stirring at room temperature for 5 min, then adding 2000 mg of a cationic adsorbent, stirring at room temperature for 5 min, taking a dried mixed cellulose ester membrane with a filtration accuracy of 5 μm, weighing it, filtering it, then drying the filtered mixed cellulose ester membrane and weighing it, calculating the weight change, which is the insoluble matter content in every 1000 g of the nitrogen oxide reducing agent urea aqueous solution to be tested, and then calculating the turbidity at 20° C. according to the insoluble matter content and a linear fitting formula; The preparation method of the anionic dispersant comprises the following steps: adding nano silicon dioxide, anhydrous ethanol, deionized water and ammonia water into a reactor, controlling the temperature in the reactor to 45° C., controlling the stirring speed to 100 rpm, stirring for 10 minutes, adding 3-aminopropyltrimethoxysilane, continuing stirring for 5 hours, continuously introducing nitrogen into the reactor while stirring, controlling the nitrogen introduction speed to 900 mL / min, adjusting the nitrogen introduction speed to 300 mL / min after 10 minutes, adding sodium allyl sulfonate, stirring for 5 hours, adding into a centrifuge, controlling the speed of the centrifuge to 12000 rpm, centrifuging for 20 minutes, taking a precipitate, washing with deionized water and drying, sealing and packaging to obtain an anionic dispersant; In the preparation of the anionic dispersant, the dosage ratio of nano-silicon dioxide, anhydrous ethanol, deionized water, ammonia water, 3-aminopropyltrimethoxysilane, and sodium allyl sulfonate is 100g:1000mL:40mL:2mL:120mL:100g; The average particle size of the nano silicon dioxide is 40 nm; The mass concentration of the ammonia water is 30%; The preparation method of the cationic adsorbent comprises the following steps: adding a calcium chloride aqueous solution into a reactor, controlling the temperature in the reactor to 20°C, controlling the stirring speed to 20 rpm, then dripping a sodium alginate aqueous solution, stirring for 17 hours after the dripping is completed, dripping a cationic polyacrylamide aqueous solution, stirring for 2 hours after the dripping is completed, filtering, taking the filter residue, washing it with deionized water and drying it, then adding it into a reactor, adding deionized water again, controlling the temperature in the reactor to 50°C, controlling the stirring speed to 20 rpm, stirring for 20 minutes, dripping a glutaraldehyde aqueous solution, continuing to stir for 5 hours after the dripping is completed, filtering, taking the filter residue, washing it with deionized water and drying it, and sealing and packaging it to obtain the cationic adsorbent; In the preparation of the cationic adsorbent, the amount ratio of the calcium chloride aqueous solution, the sodium alginate aqueous solution, the cationic polyacrylamide aqueous solution, the deionized water, and the glutaraldehyde aqueous solution is 2000mL:400mL:150mL:1000mL:470mL; The mass concentration of the calcium chloride aqueous solution is 5%; The mass concentration of the sodium alginate aqueous solution is 2%; The dropping speed of the sodium alginate aqueous solution is 9 mL / min; The mass concentration of the cationic polyacrylamide aqueous solution is 1%; The dropping speed of the cationic polyacrylamide aqueous solution is 8 mL / min; The number average molecular weight of the cationic polyacrylamide in the cationic polyacrylamide aqueous solution is 3 million, and the cationic degree is 20%; The mass concentration of the glutaraldehyde aqueous solution is 5%; The dropping speed of the glutaraldehyde aqueous solution is 5 mL / min; A mixed cellulose ester membrane with a filtration accuracy of 5 μm was used in the filtration; The linear fitting formula is: turbidity at 20° C.=1.201×insoluble matter content+0.207.

[0012] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for rapidly evaluating the turbidity of the nitrogen oxide reducing agent urea aqueous solution of the present invention disperses and adsorbs the insoluble matter in the nitrogen oxide reducing agent urea aqueous solution by using an anionic dispersant and a cationic adsorbent, thereby realizing rapid detection of the turbidity of the nitrogen oxide reducing agent urea aqueous solution without relying on a turbidimeter, and the detection result is accurate. In the preparation of the anionic dispersant, 3-aminopropyltrimethoxysilane is first used to react with the hydroxyl group on the surface of nano-silica, thereby grafting amino groups on the surface of the nano-silica and reducing the adsorption of urea, and then sodium allyl sulfonate is used to perform Michael addition with the amino group, thereby grafting sodium sulfonate, that is, anionic groups. In the preparation of the cationic adsorbent, calcium ions are first used to cross-link sodium alginate , obtain cross-linked microspheres, then use the cross-linked microspheres to adsorb cationic polyacrylamide, and finally use glutaraldehyde to fully cross-link to reduce the exposure of polar groups and avoid the adsorption of urea to obtain a cationic adsorbent. During the detection, first use an anionic dispersant for dispersion. The anionic dispersant, as a nano-dispersant, can adhere to the surface of the insoluble matter. Then use a cationic adsorbent for adsorption and adsorb the remaining anionic dispersant, thereby improving the accuracy of the test results and achieving the adsorption of all insoluble matter. The cationic adsorbent has a large particle size and can be removed by using a filter membrane with a lower filtration accuracy after adsorption. The filtration difficulty is small, thereby shortening the detection time. Due to the strong adsorption capacity of the cationic adsorbent, rapid adsorption can be achieved without multiple washings. (2) The method for rapidly evaluating the turbidity of the aqueous solution of urea, a nitrogen oxide reducing agent, according to the present invention does not need to be prepared and used immediately, but can be sealed and stored after preparation and used directly when needed, thereby further shortening the detection time; (3) The error between the rapid evaluation method of the turbidity of the urea aqueous solution of the nitrogen oxide reducing agent of the present invention and the actual insoluble content is small. The error rate between the insoluble content obtained at 20°C according to the method of the present invention and the actual insoluble content is 0.67-1.63%; (4) The method for rapidly evaluating the turbidity of the aqueous solution of urea as a nitrogen oxide reducing agent of the present invention adopts a method in which a cationic adsorbent is used to adsorb insoluble matter. The cationic adsorbent has a strong adsorption capacity and its adsorption capacity is less affected by temperature. The error rate between the insoluble matter content obtained at 10°C according to the method of the present invention and the actual insoluble matter content is 0.63-2.00%. DETAILED DESCRIPTION

[0013] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0014] Example 1 A rapid evaluation method for the turbidity of a urea aqueous solution as a nitrogen oxide reducing agent is provided, specifically: 1. Determine linear correlation: Use AUS 32 special urea, pure water, and insoluble matter to prepare 7 portions of nitrogen oxide reducing agent urea aqueous solution, marked as samples 1-7. The mass of samples 1-7 is 2000kg, and the insoluble matter content is 0.00mg / kg, 4.00mg / kg, 8.00mg / kg, 12.00mg / kg, 16.00mg / kg, 20.00mg / kg, and 24.00mg / kg respectively. According to the national standard GB 29518-2013 "Urea aqueous solution of nitrogen oxide reducing agent for diesel engine (AUS 32)》, the insoluble matter was tested at 20℃, and the detected insoluble matter contents were 0.00mg / kg, 3.95mg / kg, 7.81mg / kg, 11.77mg / kg, 15.84mg / kg, 19.76mg / kg, and 23.73mg / kg, respectively. Then the turbidity of samples 1-7 at 20℃ was tested using a turbidity meter, and the test results are as follows:

[0015] With the insoluble content as the horizontal axis and the turbidity at 20°C as the vertical axis, a scatter plot was drawn, and then a linear fitting was performed. The linear fitting formula obtained was: turbidity at 20°C = 1.201 × insoluble content + 0.207, and the determination coefficient was 0.999, indicating that there was a linear correlation between the insoluble content and the turbidity at 20°C; 2. Feasibility determination: At 20°C, take 1000g of each of the samples 1-7 in the first step of determining the linear correlation, then add 100mg of anionic dispersant to each of them, stir at room temperature for 5min, then add 2000mg of cationic adsorbent, stir at room temperature for 5min, take 7 pieces of dry mixed cellulose ester membranes with a filtration accuracy of 5μm, weigh them respectively, filter them, then dry and weigh the filtered mixed cellulose ester membranes, calculate the weight change, and the calculation results are as follows:

[0016] The error rate between the actual insoluble content is calculated. The error rate calculation formula is: the difference between the weight change in the above table and the actual insoluble content / actual insoluble content × 100%. The calculation results are as follows:

[0017] It can be seen from the above calculation results that the obtained weight change is basically consistent with the actual insoluble content in the first step of determining the linear correlation and the insoluble content when tested according to the method specified in the national standard GB 29518-2013 "Urea Aqueous Solution of Nitrogen Oxide Reducing Agent for Diesel Engines (AUS32)", indicating that the above method is feasible for detecting the insoluble content in the urea aqueous solution of nitrogen oxide reducing agent; The preparation method of the anionic dispersant is as follows: 100g of nano-silicon dioxide, 1000mL of anhydrous ethanol, 40mL of deionized water, and 2mL of ammonia water are added to a reactor, the temperature in the reactor is controlled to 45°C, the stirring speed is controlled to 100rpm, stirring is performed for 10min, 120mL of 3-aminopropyltrimethoxysilane is added, stirring is continued for 5h, nitrogen is continuously introduced into the reactor while stirring, the nitrogen introduction speed is controlled to 900mL / min, after 10min, the nitrogen introduction speed is adjusted to 300mL / min, 100g of sodium allyl sulfonate is added, stirring is performed for 5h, the reaction mixture is added to a centrifuge, the speed of the centrifuge is controlled to 12000rpm, centrifugation is performed for 20min, a precipitate is taken, the precipitate is washed with deionized water, dried, and sealed and packaged to obtain the anionic dispersant; The average particle size of the nano silicon dioxide is 40 nm; The mass concentration of the ammonia water is 30%; The preparation method of the cationic adsorbent is as follows: 2000 mL of a 5% calcium chloride aqueous solution is added into a reactor, the temperature in the reactor is controlled to 20° C., the stirring speed is controlled to 20 rpm, and then 400 mL of a 2% sodium alginate aqueous solution is added dropwise, the dropping speed is controlled to 9 mL / min, and the mixture is stirred for 17 h after the dropping is completed, 150 mL of a 1% cationic polyacrylamide aqueous solution is added dropwise, the dropping speed is controlled to 8 mL / min, and the mixture is stirred for 2 h after the dropping is completed, and a filtration accuracy of 5 μm is used. The mixed cellulose ester membrane was filtered, and the filter residue was taken, washed with deionized water and dried, and then added to the reactor, and then 1000 mL of deionized water was added, the temperature in the reactor was controlled to 50°C, the stirring speed was controlled to 20 rpm, and stirred for 20 min, 470 mL of 5% glutaraldehyde aqueous solution was added dropwise, and the dropping speed was controlled to 5 mL / min. After the dropping was completed, stirring was continued for 5 h, and the mixed cellulose ester membrane was filtered with a filtration accuracy of 5 μm, and the filter residue was taken, washed with deionized water and dried, and sealed and packaged to obtain a cationic adsorbent; The number average molecular weight of the cationic polyacrylamide in the cationic polyacrylamide aqueous solution is 3 million, and the cationic degree is 20%; 3. Test: Take 1000g sample from the nitrogen oxide reducing agent urea aqueous solution to be tested, add 100mg of the anionic dispersant prepared in the second step of judging the feasibility, stir at room temperature for 5min, then add 2000mg of the cationic adsorbent prepared in the second step of judging the feasibility, stir at room temperature for 5min, take a dry mixed cellulose ester membrane with a filtration accuracy of 5μm, weigh it, filter it, then dry the filtered mixed cellulose ester membrane and weigh it, calculate the weight change, the weight change is the insoluble matter content in every 1000g of the nitrogen oxide reducing agent urea aqueous solution to be tested, and then calculate the turbidity at 20°C through the insoluble matter content and the linear fitting formula obtained in the first step of judging the linear correlation.

[0018] Comparative Example 1 Based on the rapid evaluation method of the turbidity of the urea aqueous solution of nitrogen oxide reducing agent in Example 1, changes are made, and the changes are as follows: The preparation of the anionic dispersant was omitted, and an equal mass of sodium dodecyl sulfate was used instead of the addition of the anionic dispersant in the second step of judging the feasibility and the third step of testing.

[0019] In the second step of judging the feasibility, the weight change after filtering and drying using a dry mixed cellulose ester membrane with a filtration accuracy of 5 μm is:

[0020] It can be seen from the calculation results that the obtained weight change is inconsistent with the insoluble matter content when detected according to the method specified in the national standard GB 29518-2013 "Urea Aqueous Solution of Nitrogen Oxide Reductant for Diesel Engines (AUS 32)" in the first step of determining the linear correlation, indicating that the feasibility of detecting the insoluble matter content in the urea aqueous solution of nitrogen oxide reductant by the above method is poor.

[0021] Comparative Example 2 Based on the rapid evaluation method of the turbidity of the urea aqueous solution of nitrogen oxide reducing agent in Example 1, changes are made, and the changes are as follows: The preparation method of the cationic dispersant is changed to: 2000 mL of deionized water and 95 g of activated carbon were added to a reactor, the temperature in the reactor was controlled to 20°C, the stirring speed was controlled to 20 rpm, and the reaction was stirred for 17 h. 150 mL of a 1% cationic polyacrylamide aqueous solution was added dropwise at a dropping speed of 8 mL / min. After the addition was completed, the mixture was stirred for 2 h. The mixture was filtered using a mixed cellulose ester membrane with a filtration accuracy of 5 μm. The residue was washed with deionized water and dried, and sealed and packaged to obtain a cationic adsorbent. The average particle size of the activated carbon is 50 μm; The number average molecular weight of the cationic polyacrylamide in the cationic polyacrylamide aqueous solution is 3 million, and the cationic degree is 20%; In the second step of judging the feasibility, the weight change after filtering and drying using a dry mixed cellulose ester membrane with a filtration accuracy of 5 μm is:

[0022] It can be seen from the calculation results that the obtained weight change is inconsistent with the insoluble matter content when detected according to the method specified in the national standard GB 29518-2013 "Urea Aqueous Solution of Nitrogen Oxide Reductant for Diesel Engines (AUS 32)" in the first step of determining the linear correlation, indicating that the feasibility of detecting the insoluble matter content in the urea aqueous solution of nitrogen oxide reductant by the above method is poor.

[0023] Test Example 1 The temperature in the feasibility determination step in step 2 of Example 1 was changed from 20°C to 10°C, and the weight change results and the error rate between the actual insoluble content were as follows:

[0024] Unless otherwise specified, all percentages used in the present invention are by mass.

[0025] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for quickly evaluating the turbidity of a nitrogen oxide reducing agent urea aqueous solution, characterized in that: Take 1000g of sample from the nitrogen oxide reducing agent urea aqueous solution to be tested, add 100mg of anionic dispersant, stir at room temperature for 5min, then add 2000mg of cationic adsorbent, stir at room temperature for 5min, take a dry mixed cellulose ester membrane with a filtration accuracy of 5μm, weigh it, filter it, then dry and weigh the filtered mixed cellulose ester membrane, calculate the weight change, the weight change is the insoluble matter content in every 1000g of the nitrogen oxide reducing agent urea aqueous solution to be tested, and then calculate the turbidity at 20°C by the insoluble matter content and the linear fitting formula; The preparation method of the anionic dispersant comprises mixing nano-silicon dioxide, anhydrous ethanol, deionized water and ammonia water, stirring at 45° C., adding 3-aminopropyltrimethoxysilane, continuing stirring, and then adding sodium allyl sulfonate in a nitrogen environment, stirring, centrifuging, taking a precipitate, washing, drying, and sealing and packaging to obtain the anionic dispersant; In the preparation of the anionic dispersant, the dosage ratio of nano-silicon dioxide, anhydrous ethanol, deionized water, ammonia water, 3-aminopropyltrimethoxysilane, and sodium allyl sulfonate is 100g:1000mL:40mL:2mL:120mL:100g; The preparation method of the cationic adsorbent comprises the following steps: stirring a calcium chloride aqueous solution at 20° C., then dripping a sodium alginate aqueous solution into the calcium chloride aqueous solution, stirring after the dripping is completed, dripping a cationic polyacrylamide aqueous solution, stirring after the dripping is completed, filtering, taking a filter residue, washing and drying, then mixing with deionized water, stirring at 50° C., dripping a glutaraldehyde aqueous solution, continuing to stir after the dripping is completed, filtering, taking a filter residue, washing and drying, and sealing and packaging to obtain the cationic adsorbent; In the preparation of the cationic adsorbent, the dosage ratio of the calcium chloride aqueous solution, the sodium alginate aqueous solution, the cationic polyacrylamide aqueous solution, the deionized water, and the glutaraldehyde aqueous solution is 2000mL:400mL:150mL:1000mL:470mL.

2. The method for rapidly evaluating the turbidity of a urea aqueous solution containing a nitrogen oxide reducing agent according to claim 1, characterized in that: In the preparation of the anionic dispersant, the average particle size of the nano-silicon dioxide is 40 nm; The mass concentration of the ammonia water is 30%.

3. The method for rapidly evaluating the turbidity of a urea aqueous solution containing a nitrogen oxide reducing agent according to claim 1, characterized in that: In the preparation of the cationic adsorbent, the mass concentration of the calcium chloride aqueous solution is 5%; The mass concentration of the sodium alginate aqueous solution is 2%; The dropping speed of the sodium alginate aqueous solution is 9 mL / min; The mass concentration of the cationic polyacrylamide aqueous solution is 1%; The dropping speed of the cationic polyacrylamide aqueous solution is 8 mL / min; The number average molecular weight of the cationic polyacrylamide in the cationic polyacrylamide aqueous solution is 3 million, and the cationic degree is 20%; The mass concentration of the glutaraldehyde aqueous solution is 5%; The dropping speed of the glutaraldehyde aqueous solution is 5 mL / min; A mixed cellulose ester membrane with a filtration accuracy of 5 μm was used in the above filtration.

4. The method for rapidly evaluating the turbidity of a urea aqueous solution containing a nitrogen oxide reducing agent according to claim 1, characterized in that: The linear fitting formula is: turbidity at 20° C.=1.201×insoluble matter content+0.207.

Citation Information

Patent Citations

  • Method for detecting content of insoluble substances in urea

    CN111929281A

  • Preparation process of high-purity urea solution for vehicles

    CN113230914A

  • Method for dispersing metal nanowires in organic solvents with different polarities

    CN115319081A

  • Method for detecting cyanuric acid in high-purity urea

    CN116165196A

  • Method for measuring content of surface modifier in coated fine oxidant

    CN116337679A